Resolving West Africa's electricity dilemma through the pursuit of smart grid opportunities - Cheikh Dramé (International Telecommunications Society (ITS), 2014)
The electricity sector in West Africa provides power supply to only about 30% of the population (WAPP, Business Plan 2012 - 2015, 2012). The West African electricity dilemma refers to poor access to electricity due to an amalgamation of constraints primarily emanating from the regulatory environment and the demand and supply side of the electricity sector. This paper reviews the pertinent literatures in order to identify and communicate constraints upon access to electricity in the region, considered low by world standard. In order to alleviate West Africa's electricity dilemma, this paper suggests the pursuit of smart grid opportunities such as off-grid small-scale renewable energy technologies (RETs), smart meters, power line communication, metered-based tariffs and prepayments via mobile phones. The conceptual framework used in this paper integrates interrelated socio/economic aspects, regulatory aspects, financial aspects, and technical aspects deemed fundamental to successfully deploy smart grid technologies in West Africa, with Côte d'Ivoire as a case study. Telecommunications will play a key role in leveraging benefits of smart grid. The next step in this research will be to conduct interviews with stakeholders of the West African electricity sector as a mean to verify the extent to which smart grid opportunities are realizable in the region and enrich what can be learned through secondary research with what can only be learned from those active on the ground.
Keywords: 330; Electricity Access; Electricity Dilemma; Smart Grid; Telecommunications; West Africa